MANAJEMEN PENYELENGGARAAN LAYANAN PENDIDIKAN SEKOLAH INKLUSI - Nurhayati Nurhayati (Universitas Negeri Jakarta, 2014)
The objective of this research was to get picture of the management implementation of service education of an Inclusive School conducted in Tunas Nusantara Rumekso Institution as the organizer of Melati Indonesia School, Bekasi. This research used qualitative method with study case. The key informants were institution owner, principals from all levels and also teachers. To strengthen the result of this research, assessing data credibility is done through multiple informant, theory/concept and method triangulation. The data were collected through participant observation and had the results that (1).The Management implementation of education services in Melati Indonesia School conducted in a simple structure that refers to the vision-mission.This was reflected in the recruitment and placement of human resources within its organization. (2). Management of the organization was developed as much as possible conducted each academic year in order to structure the organization of teaching and learning well. (3). Management of human resources development still gave the priority of professional development and career coaching.